Treating depression, anxiety, and stress in ethnic and racial groups : cognitive behavioral approaches - Chang, Edward C. (Edward Chin-Ho); Downey, Christina A.; Hirsch, Jameson K.; Yu, Elizabeth A. (Cultural, racial, and ethnic psychology book series., 2018)
"Cognitive behavioral models, measures, and treatments (CBMMTs) have been widely used to conceptualize, assess for, and treat commonly experienced psychological problems, including depression, anxiety, and stress. Despite the well-established use of CBMMTs for treating psychological problems, there is a dearth of CBMMTs targeted for use with diverse ethnoracial groups. The book is divided into three main sections, each focusing on a robust concern for mental health treatment--namely, working with individuals experiencing clinically significant symptoms of depression, anxiety, or stress. Part I focuses on CBMMTs of depressive disorders. It examines CBMMTs for depressive disorders among Asian Americans, Latin Americans, African Americans, and American Indians and Alaskan Natives. Part II presents a review of CBMMTs of anxiety disorders. It examines CBMMTs for anxiety disorders among Asian Americans, Latin Americans, African Americans, and American Indians and Alaskan Natives. Part III focuses on CBMMTs for stress. It examines CBMMTs for stress among Asian Americans, Latin Americans, African Americans, and American Indians and Alaskan Natives. The book concludes with an overview of common themes and concepts addressed in previous chapters. Specifically, in the interaction of culture with context, factors that are important to consider in relation to CBMMTs for racial and ethnic groups may be factors such as acculturation, language, cultural history, historical trauma, and stigma of mental illness. The book can play an instrumental role in helping all mental health professionals, regardless of their ethnoracial status and background, to find value and guidance when working with diverse adults." --